AHP-based Selection of Outstanding Students - Utami, Dian Retno (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2023)
The decision support system employs the Analytical Hierarchy Process (AHP) method to enhance the selection of outstanding students at SMA Muhammadiyah 8 Palembang. This system acknowledges the limitations of the current evaluation process, which relies solely on academic scores and aims to rectify this by integrating additional factors like attendance, behavior, and non-academic achievements. The AHP method's systematic breakdown of criteria and sub-criteria, supported by figures and tables, elucidates the decision-making process, ensuring a more comprehensive evaluation framework. The development of this system follows the Waterfall model, emphasizing sequential phases from analysis to implementation, yet acknowledging its challenges in accommodating evolving requirements. The method section expounds on the AHP process, delineating its steps in structuring problems, conducting pairwise comparisons, creating priority matrices, and arriving at conclusive decisions. It also outlines the hierarchical model and the subsequent ranking of alternatives, showcasing how the AHP method facilitates a fairer assessment of outstanding students. The conclusion underscores the system's functionality, validated through Black Box testing, affirming its alignment with initial expectations. Overall, this comprehensive approach advocates for a more holistic method of identifying outstanding students.